User needs analysis and evaluation of portals - Zaphiris, Panayiotis; Dellaporta, Aspasia; Mohamedally, Dean (My University, 2006)
In this paper, we first present and discuss the importance of usability and accessibility in the design and evaluation of portal systems. We then present an incremental framework for taking this issues into consideration during the design of such systems and finally conclude with the application of this framework to the design of a public service portal.